Alterations in maternally perceived fetal movement and their association with late stillbirth: findings from the Midland and North of England stillbirth case–control study. Issue 7 (6th July 2018) - Heazell, Alexander E P; Budd, Jayne; Li, Minglan; Cronin, Robin; Bradford, Billie; McCowan, Lesley M E; Mitchell, Edwin A; Stacey, Tomasina; Martin, Bill; Roberts, Devender; Thompson, John M D
Abstract : Objective: To report perception of fetal movements in women who experienced a stillbirth compared with controls at a similar gestation with a live birth. Design: Case–control study. Setting: 41 maternity units in the UK. Participants: Cases were women who had a late stillbirth ≥28 weeks gestation (n=291) and controls were women with an ongoing pregnancy at the time of the interview (n=733). Controls were frequency matched to cases by obstetric unit and gestational age. Methods: Data were collected using an interviewer-administered questionnaire which included questions on maternal perception of fetal movement (frequency, strength, increased and decreased movements and hiccups) in the 2 weeks before the interview/stillbirth. Five fetal movement patterns were identified incorporating the changes in strength and frequency in the last 2 weeks by combining groups of similar pattern and risk. Multivariable analysis adjusted for known confounders. Primary outcome measure: Association of maternally perceived fetal movements in relation to late stillbirth. Results: In multivariable analyses, women who reported increased strength of movements in the last 2 weeks had decreased risk of late stillbirth compared with those whose movements were unchanged (adjusted OR (aOR) 0.18, 95% CI 0.13 to 0.26). Women with decreased frequency (without increase in strength) of fetal movements were at increased risk (aOR 4.51, 95% CI 2.38 to 8.55). Daily perception of fetal hiccups was protective (aOR 0.31, 95% CI 0.17 to 0.56). Conclusions: Increased strength of fetal movements and fetal hiccups is associated with decreased risk of stillbirth. Alterations in frequency of fetal movements are important in identifying pregnancies at increased risk of stillbirth, with the greatest risk in women noting a reduction in fetal activity. Clinical guidance should be updated to reflect that increase in strength and frequency of fetal movements is associated with the lowest risk of stillbirth, and that decreased fetal movements are associated with stillbirth. Trial registration number: NCT02025530 .